Analisis Perbandingan Pengaruh Campuran Kawat Bendrat dan Serat Baja pada Self Compacting Concrete (SCC) - Anggraeni, Sylvia Dewi; Noorhidana, Vera Agustriana; Irianti, Laksmi; Isneini, Mohd. (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2022)
Self compacting concrete (SCC) is a concrete innovation that is carried out to overcome problems during casting that does not require manual compaction even in hard-to-reach places such as tight reinforcement. In this study, 3D Dramix steel fibers and bendrat wire were used as a mixture in SCC with volume fractions of 0%, 0.5%, 1%, 1.5%. The addition of this fiber aims to determine the effect of the two fibers on SCC on compressive strength, split tensile strength and flexural tensile strength. The sample in this study was a cylinder with a diameter of 150 mm and a height of 300 mm for testing the compressive strength and split tensile strength while the flexural tensile strength used a beam sample with a size of 100x100x400 mm. All samples of these specimens were tested when the concrete was 28 days old. The increase in the value of compressive strength, split tensile strength and flexural strength at the addition of 1.5% steel fiber were 26.39%, 64.71% and 111.88% respectively for concrete with 0% fiber. While the increase in compressive strength, split tensile strength and flexural strength with the addition of 1.5% bendrat wire was 20.31%, 60.74% and 76.18% for concrete with 0% fiber, respectively.